2018
DOI: 10.1186/s12935-018-0565-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the PI3K but not the MEK/ERK pathway sensitizes human glioma cells to alkylating drugs

Abstract: BackgroundIntrinsic chemoresistance of glioblastoma (GBM) is frequently owed to activation of the PI3K and MEK/ERK pathways. These signaling cascades are tightly interconnected however the quantitative contribution of both to intrinsic resistance is still not clear. Here, we aimed at determining the activation status of these pathways in human GBM biopsies and cells and investigating the quantitative impact of both pathways to chemoresistance.MethodsReceptor tyrosine kinase (RTK) pathways in temozolomide (TMZ)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 62 publications
4
29
0
Order By: Relevance
“…When we tested MET in combination with doxorubicin in a panel of GBM cell lines and primary cells we found a sensitizing effect only for the A172 cell line and to some extend in primary GBM cells. We have previously shown that P-gp is not expressed in U87, U251 and U373 cell lines [18] which might explain why these cells could not be sensitized to doxorubicin by MET, while inhibition of doxorubicin e ux has previously been reported for the A172 cell line [10]. Our ndings are in line with a study which also reported no sensitizing effect of MET on various doxorubicintreated canine tumor cells [12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When we tested MET in combination with doxorubicin in a panel of GBM cell lines and primary cells we found a sensitizing effect only for the A172 cell line and to some extend in primary GBM cells. We have previously shown that P-gp is not expressed in U87, U251 and U373 cell lines [18] which might explain why these cells could not be sensitized to doxorubicin by MET, while inhibition of doxorubicin e ux has previously been reported for the A172 cell line [10]. Our ndings are in line with a study which also reported no sensitizing effect of MET on various doxorubicintreated canine tumor cells [12].…”
Section: Discussionsupporting
confidence: 89%
“…All other cells and cell lines were cultivated in Dulbecco's Modi ed Eagle Medium (DMEM) low glucose (Biowest, Nuaillé, France) containing 10% FCS (Biochrom, Berlin, Germany), 100 IU/ml penicillin, and 100 µg/ml streptomycin (Biowest, Nuaillé, France). Primary GBM cells derived from a primary GBM tumor biopsy were obtained from the University Hospital Cologne, genetically characterized and cultured as previously described [18].…”
Section: Methodsmentioning
confidence: 99%
“…GBM cell lines and high-grade glioma tissue have been reported to express significant amounts of Trx [ 16 , 28 , 29 ]. In order to confirm this, we determined Trx and TXNIP expression in three established GBM cell lines—U87, U251, and U373—and primary GBM cells, which have previously been shown by us to be intrinsically resistant to TMZ and cisplatin [ 30 ]. Trx-1 and TXNIP protein was expressed in all cells as determined by Western blotting ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, TMZ is the only substance for which a statistically significant and clinically relevant benefit in both overall survival and progression-free survival has been demonstrated [ 4 ]. However, it is very difficult to handle in the laboratory setting as it must be given to GBM cells in concentrations as high as or even beyond its solubility [ 30 ]. Thus, we also used cisplatin as a model substance with a similar molecular mechanism of action: both substances interfere with DNA, resulting in strand breaks and apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation